‘Positive Education’: A Professional Learning Programme to Foster Teachers’ Resilience andWell-Being - Fernandes, Luísa (2021)
Professional learning can make a significant contribution to teachers’ resilience and well-being. This chapter reports the implementation of a professional learning programme focused on resilience and well-being, targeting 35 inservice Portuguese teachers, mostlyworking in middle and secondary education. The ‘Positive Education’ programme was adapted from the European project ENTREE (ENhancing Teachers REsilience in Europe) and encompasses six training modules: 1—Resilience; 2—Building Relationships; 3—Emotional Well-Being; 4—Stress Management; 5—Effective Teaching; 6—Classroom Management, and an additional module named ‘Education forWell-Being’. The concepts and topics for each module will be discussed, along with the design and implementation of the strategies followed to promote a positive, collaborative and reflexive environment (e.g. wellness activities, stress relief and work–life balance). This chapter also describes the main effects of the training programme on participants, gathered through interviews at the end of the training sessions.